Effect of coating pigment, binder type and binder amount on planar liquid wicking on coated substrates - Jutila, Eveliina; Koivunen, Risto; Gane, Patrick A.C. (Journal of Print and Media Technology Research, 2023)
This study focuses on the development of highly wicking coated substrates for microfluidic devices with enhanced resolution compared to current filter paper-based devices. Four highly absorbing pigments, fumed silica (FS), modified calcium carbonate (MCC), natural diatomite (ND) and flux-calcined diatomite (FCD), as well as three binders, styrene-acrylate (SA) latex, polyvinyl alcohol (PVOH) and carboxymethyl cellulose (CMC), were used to form coating structures with different wicking properties. Studies include characterisation of the pigment particles and thin layer wicking (TLW) experiments, in which wicking height of liquid in coatings is measured as a function of time. The results show that the choice of coating pigment and binder as well as the binder amount has a significant effect on wicking characteristics of a coating. The introduction of diatomite pigments into blends with MCC improved the wicking capabilities of the coating, especially in the case of ND. Latex was found to inhibit wicking of liquid the least, followed by PVOH and CMC. Increased binder amounts reduce wicking due to reduced pore connectivity and binder-filled pores. It was found that the wicking resistance of pigment alone is too high for rapid analysis over long distances in thick coatings. Once optimised for binder type and amount, these coating structures could be utilised as high resolution microfluidic analysis elements, i.e. test cells, incorporated either into a wicking channel matrix or placed at junctions of microfluidic channels derived from controlled hydrophobic/ oleophobic printing or designed shrinkage fracture geometries.